La cesión de créditos personales y su incidencia frente a las sentencias emitidas, en la Unidad Judicial Civil del canton Riobamba, en el año 2015 - Carrasco Sanunga, Santos Mauricio (2018)
The loan agreement is an instrument in which the creditor and debtor qualities are determined, due to the obligation contained in this instrument. This document is important, because the assignment of personal loans, which is the subject of this research work is produced on the loan contract, since other legal documents, which are also transferred have their own form, as is the case of the Check, which is endorsed, to another holder. It was necessary to speak in the same way of the guarantees of the loan contract, which will also be assigned jointly with the main obligation, since the object of the assignment of personal credit, is oriented to the transfer of the obligation, and includes obligations Accessories. Mortgage is a real security that is established on a real estate, so that in the case of non-compliance with the obligation this guarantee can be executed and pay with the product of its auction the main obligation, it should be added that the mortgage allows the debtor to keep The good, even when it must be seized as a pre-shot, as it is a root good that there is no danger of it disappearing. The pledge is different from the mortgage for the object on which it is, so the pledge is a security right that is constituted solely on movable property; That is, goods that can move. Finally, the assignment of personal credit, which basically transcends the obligation contained in the loan contract, as well as the real guarantees, be these the mortgage or the pledge. The assignment of rights is a written agreement whereby the creditor assigns a security that contains the obligation contracted by a debtor to a third person called a transferee, so that the latter in turn executes the obligation when the time or Condition that they return to that obligation.